Examination of Physical Therapists Understanding of Geriatric Patient Advocacy - Kristen Karnish (Adult Education Research Conference, 2014)
The goal of this study is to examine the attitudes, beliefs and actions of physical therapists regarding advocacy for geriatric patients. Patient advocacy is a multifaceted component of health care embedded in the role of health care practitioners. Mixed methods research will utilize a critical gerontology perspective to explore the complexity of factors involved in geriatric patient advocacy.